Leadership and Innovation Dynamics on Public Servants: Creative Self-Efficacy and Affective Commitment as Mediators - Elvirani Dwi Saputri; Elok Savitri Pusparini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study explores how creative self-efficacy and affective commitment mediate the relationship between leadership styles and innovative work behavior among public servants in the government financial sector. It compares the impact of self-leadership and transformational leadership on innovative work behavior, using public servants as the research subjects. The study surveyed 860 public servants in a state financial organization using online questionnaires with a 7-point Likert scale. Data were analyzed using SmartPLS and Structural Equation Modelling (SEM). The study found a positive link between creative self-efficacy, affective commitment, and innovative work behavior, highlighting the mediating role of creative self-efficacy and affective commitment between leadership style and innovative work behavior. It recommends that supervisors adopt a transformational leadership style to enhance creative self-efficacy and affective commitment, thereby boosting innovative work behavior. Additionally, organizations should employ self-leadership strategies to promote innovation.